Numerical Investigation of Sand Erosion Effects on the T-56 Compressor Blade with Changing Parameters - Qattan, Nizar A.; Kada, Belkacem; Al-Bahi, Ali M. (Transactions on Engineering and Computing Sciences, 2025)
This paper presents a comprehensive numerical investigation into the effects of sand erosion on the T-56 compressor blade, a critical component in turbomachinery subjected to harsh environmental conditions. Using advanced Computational Fluid Dynamics (CFD) techniques, the study examines the impact of parameters such as sand particle concentration, size, and pressure ratio on blade erosion rates and overall compressor performance. The numerical analysis is validated against established NASA Rotor 37 data, providing confidence in the accuracy of the modeling approach. Results reveal the significant influence of sand erosion on aerodynamic efficiency and highlight key operational considerations to mitigate damage in sandy environments. This research provides valuable insights for improving the design and maintenance of turbomachinery, particularly in regions like the GCC, where sand ingestion poses a severe challenge.